2016
DOI: 10.21521/mw.5518
|View full text |Cite
|
Sign up to set email alerts
|

effect of ascorbic acid as a feed additive on indicators of the reproductive performance of Pulawska breed gilts

Abstract: Effect of ascorbic acid as a feed additive on indicators of the reproductive performance of Pulawska breed gilts Summary The aim of the study was to determine the effect of vitamin C on indicators of gilts and sows reproductive value. The study was conducted using 64 gilts of the Pulawska breed. The experimental gilts received a supplement of vitamin C in an amount of 2.4 g daily throughout the whole experiment. Sixteen gilts from both control and experimental groups were mated in their third estrus. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The improvement of antioxidant enzyme activity in colostrum and milk is beneficial to piglets, which contributes to the antioxidant status of piglets and thus increases the daily weight gain of piglets from birth to weaning [ 9 , 55 ]. Evidence has shown that supplementation with antioxidants, such as selenium, vitamin E and vitamin C, improves antioxidant status and reproductive performance in sows [ 11 , 55 , 56 ]. Similarly, a growing number of studies have demonstrated that certain functional substances, such as isoflavone [ 9 ], ginger extract [ 57 ] and chitosan [ 58 ], alleviate oxidative stress and improve the reproductive performance of sows.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of antioxidant enzyme activity in colostrum and milk is beneficial to piglets, which contributes to the antioxidant status of piglets and thus increases the daily weight gain of piglets from birth to weaning [ 9 , 55 ]. Evidence has shown that supplementation with antioxidants, such as selenium, vitamin E and vitamin C, improves antioxidant status and reproductive performance in sows [ 11 , 55 , 56 ]. Similarly, a growing number of studies have demonstrated that certain functional substances, such as isoflavone [ 9 ], ginger extract [ 57 ] and chitosan [ 58 ], alleviate oxidative stress and improve the reproductive performance of sows.…”
Section: Discussionmentioning
confidence: 99%
“…Levine et al (1996) reported that vitamin C elevates the protein content in plasma by altering serum total protein components and ratio. Lechowski et al (2015) proved this by an increased level of protein in colostrum, milk and also increased fat components. This improves the survivability of piglets by facilitating rapid growth and development.…”
Section: Introductionmentioning
confidence: 83%
“…The antioxidant properties of vitamin C and the potential against oxidative stress and infection have been established in livestock. It is also important under other stressful conditions like heat, weaning, parturition and lactation (Lechowski et al, 2015;Ahmadu et al, 2016). It was previously thought for many years that pigs are able to synthesize enough vitamin C, however, their deficiency has been proved to be unsafe (Ching et al, 2001;Kolb and Seehawer, 2001;Lauridsen and Jensen, 2005;Chung, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a positive subsequent impact of the vitamins provided to sows was noted: a combination of vitamin E and C significantly lowered the body temperature of sows following farrowing and notably decreased the number of sows culled after rearing [125]. A study by Lechowski et al (2016) demonstrates that vitamin C supplementation in gilts and sows improves reproductive performance. This included an increase in the number of corpora lutea and the synthesis of 17b-estradiol.…”
Section: Vitamin Cmentioning
confidence: 99%